Trade is a two-way exchange : rising import penetration in East Asia's export economies. - HILL, Hal (1993)
Points out that while East Asia's exports have grown quickly, one feature has been high and rapidly increasing import penetration. Imports have risen sharply in these countries both to lay the base for the export growth, and because the economies of East Asia have become increasingly open and internationally oriented. In the process, the OECD economies have benefitted from this export growth. Consequently, any measures which impede East Asia exports will, at an aggregate level, harm both groups of economies.